THU0573 15-year trends and correlates of school sports attendance among children and adolescents with jia enrolled in the german national paediatric rheumatologic database. (12th June 2018) - Milatz, F.; Klotsche, J.; Niewerth, M.; Geisemeyer, N.; Hansmann, S.; Hartmann, M.; Kallinich, T.; Peitz, J.; Trauzeddel, R.; Minden, K.
Abstract : Background: Besides leisure-based physical activities (PA), the school-setting is described as one of the most effective areas for providing opportunities for PA, collectively reaching school-aged children vulnerable to sedentary behaviours. 1 In this context, regular participation in school sports can help children and adolescents achieve a part of the recommended amount of daily physical activity and help gain the knowledge and attitudes they need to engage in lifelong active lifestyle. Objectives: Since adolescents with juvenile idiopathic arthritis (JIA) are less involved in physical and social activities compared to their healthy peers, the objectives were as follows: 1 to describe the extent to which school sports attendance among patients with JIA changed over time, and 2 to determine correlates associated with exemption from school sports. Methods: Data of school-aged children and adolescents with JIA recorded in the National Paediatric Rheumatologic Database (NPRD) in the years 2000 to 2015 were considered for the analyses. Whether school sports participation had changed between 2000 and 2015 was determined using linear mixed models. Data from 2015 were inspected to analyse correlates of school sports absenteeism. Results: During the observation period, participation rates in school sports were determined in 23.016 patients. The proportion of patients who participated always steadily increased from 31% in 2000 to 64% in 2015 (β=0.017, 95% confidence interval (CI) 0.015, 0.020), whereas the exemption rate simultaneously decreased from 44% in 2000 to 16% in 2015 [β=−0.009, 95% CI −0.011, –0.007]. In 2015, data from 5879 patients (mean age 13.1±3.3 years, disease duration 5.9±4.0 years, persistent oligoarthritis 37%) were available for evaluation. Fully exemption was associated with functional limitations, disease activity and any use of DMARDs, intra-articular glucocorticoid injection or physiotherapy. Conclusions: School sports attendance among children and adolescents with JIA has increased significantly over the last 15 years. Possible explanations may include improved functional ability, probably due to earlier and more frequent use of DMARDs. Considering the impact of JIA on daily life, the sedentary habits that come with it, and the potentially favourable effect of PA, it is important to promote an active lifestyle in children with JIA. In order to encourage patients to attend more frequently, it will be necessary to provide comprehensive information among teachers, parents and physicians regarding opportunities and risks of school sports. Reference: [1] Mei H, et al. The impact of long-term school-based physical activity interventions on body mass index of primary school children - a meta-analysis of randomized controlled trials. BMC Public Health2016;16:205. Acknowledgements: The National Paediatric Rheumatological Database has been funded by the German Children Arthritis Foundation (Deutsche Kinder-Rheumastiftung), AbbVie, Pfizer and Chugai. Disclosure of Interest: F. Milatz: None declared, J. Klotsche: None declared, M. Niewerth: None declared, N. Geisemeyer: None declared, S. Hansmann: None declared, M. Hartmann: None declared, T. Kallinich: None declared, J. Peitz: None declared, R. Trauzeddel: None declared, K. Minden Grant/research support from: German Rheumastiftung, Pfizer, AbbVie, Roche, Speakers bureau: AbbVie, Medac, Pharm-Allergan